Bio-preservation effect of lactic acid bacteria postbiotics on physical, chemical, and sensory properties of vacuum-packaged broiler breast meat - Rahman, Md Moklesur; Sazili, Awis Qurni; Ahmad, Siti Aqlima; Abdul Khalil, Khalilah; Ismail-Fitry, Mohammad Rashedi; Afsana, Ayesha Shiddika; Islam, Aminul; Foruzanfard, Mahdi; Sarker, Md Sazedul Karim (Elsevier B.V., 2025)
Increasing consumer demand for quality broiler meat has driven interest in natural preservatives, particularly postbiotics of lactic acid bacteria (LAB). This study explored the use of concentrated cell-free supernatants (CFS) from Lactobacillus acidophilus (LA) and Lacticaseibacillus rhamnosus GG (LGG) as marinades to improve the physicochemical and sensory attributes of vacuum-packaged broiler breast meat. Meat samples (35 g) were marinated with CFS (500 µL/mL; 5:1 ratio), vacuum-sealed, and stored at 4°C for 10 days. Evaluations were conducted on days 0, 3, 7, and 10. Key indicators, including pH, water-holding capacity (WHC), drip loss (DL), cooking loss (CL), lipid oxidation (TBARS), color, and texture, were analyzed using standard techniques (TBARS assay, colorimetry, texture profile analysis). Sensory panels evaluated the color, texture, odor, and acceptability. Both postbiotics significantly enhanced meat quality by lowering pH (6.03-6.04), TBARS value (0.694-0.678 mg MDA/kg), and DL (2.38-2.46 %), while increasing WHC (73.09-71.01 %) than the control (6.28, 0.829 mg MDA/kg, 3.02 %, and 59.94 %, respectively). Postbiotics preserved color, with higher a* (3.12-3.74 vs 1.68) and b* (16.32-16.95 vs 13.87) values, with improved texture of both raw and cooked meat. LGG postbiotics showed superior antioxidative effects, while LA postbiotics improved sensory attributes (color score: 4.00 vs 2.33 in control). The practical application of LA and LGG postbiotics as natural bio-preservatives in meat processing, offering clean-label solutions for prolonging shelf life and quality enhancement in broiler meat. Although the specific metabolites were not identified, these findings mark a novel, targeted approach to postbiotics use in meat preservation.